Linguistic complexity in high-school students’ EFL writing - Delić Amer; Jašić Alma Jahić (ExELL (Explorations in English Language and Linguistics))
This study examined the syntactic and semantic complexity of L2 English writing in a Bosnian-Herzegovinian high school. Forty texts written by individual students, ten per grade, were quantitatively analyzed by applying methods established in previous research. The syntactic portion of the analysis, based on the t-unit analysis introduced by Hunt (1965), was done using the Web-based L2 Syntactic Complexity Analyzer (Lu, 2010), while the semantic portion, largely based on the theory laid out in systemic functional linguistics (Halliday & Matthiessen, 2014), was done using the Web-based Lexical Complexity Analyzer (Ai & Lu, 2010) as well as manual identification of grammatical metaphors. The statistical analysis included tests of variance, correlation, and effect size. It was found that the syntactic and semantic complexity of writing increases in later grades; however, this increase is not consistent across all grades.